HUBUNGAN ANTARA GENDER DAN KEPRIBADIAN DENGAN GAYA KEPEMIMPINAN DI PT MULTI CITRA ABADI MANADO - Eddy Madiono Sutanto; Dewi Mistyca Miliangan Liang (STIE Perbanas Surabaya, 2014)
This study aims to find the relationship that exists between gender and personality as well asthe supervisor leadership styles in PT Multi Citra Abadi Manado. The study is a quantitativeresearch and uses questionnaire as data collection instrument. The population consists of 700employees who work at PT Multi Citra Abadi Manado and the sample was 56 supervisors ofPT Multi Citra Abadi Manado. The study used descriptive and statistical analysis. Descriptiveanalysis was done by using cross tabulation while the statistical analysis by using correlationanalysis. Hypothesis test was done by using chi-square test and regression analysis. The resultshows that there is a relationship between gender and personality, and it is also indicated thatthere is a relationship between gender and leadership style. The study shows the relationshipbetween supervisor personality and leadership style in PT Multi Citra Abadi Manado. Basedon the research, being open is considered a value of personality that should be increased forcustomers in global era.